Illocutionary Act Analysis of Melati and Isabel Wijsen Speech at United Nations - Damayanti, Luh Sri (STKIP Agama Hindu Singaraja, 2024)
This study was conducted to analyze the illocutionary act used in Melati and Isabel Wijsen’s United Nations Speech. This speech was performed on World Oceans Day 2017. From the illocutionary act that was analyzed, the readers are able to learn that utterances also play role as actions that can influence people to do something. The qualitative descriptive method was used in this study to collect and analyze the data, followed the model from (Miles et al., 2014). This qualitative model consists of data condensation, data display, and drawing conclusion. The researcher used the illocutionary act types that were proposed by (Searle, 1976) as the grounded theory in making the classification of illocutionary utterances found in Melati and Isabel Wijsen’ speech. As a result, researcher found 18 assertives (56, 25%), 7 declaratives (21, 88%), 4 commissives (12, 5%), 3 expressives (9, 38%), 0 declaratives (0%). From the results found, Melati and Isabel Wijsen tend to use their speech to convince the audience by informing, believing, reporting, showing, and stating. This study suggests that applying illocutionary acts could make a speech more powerful.